Quantitative proteomics identifies TCF1 as a negative regulator of Foxp3 expression in conventional T cells - Delacher, Michael; Barra, Melanie M.; Herzig, Yonatan; Eichelbaum, Katrin; Rafiee, Mahmoud-Reza; Richards, David; Träger, Ulrike; Hofer, Ann-Cathrin; Kazakov, Alexander; Braband, Kathrin L.; Gonzalez, Marina; Wöhrl, Lukas; et al. (iScience, 2020)
Regulatory T cells are important regulators of the immune system and have versatile functions for the homeostasis and repair of tissues. They express the forkhead box transcription factor Foxp3 as a lineage-defining protein. Negative regulators of Foxp3 expression are not well understood. Here, we generated double-stranded DNA probes complementary to the Foxp3 promoter sequence and performed a pull-down with nuclear protein in vitro, followed by elution of bound proteins and quantitative mass spectrometry. Of the Foxp3-promoter-binding transcription factors identified with this approach, one was T cell factor 1 (TCF1). Using viral over-expression, we identified TCF1 as a repressor of Foxp3 expression. In TCF1-deficient animals, increased levels of Foxp3intermediateCD25negative T cells were identified. CRISPR-Cas9 knockout studies in primary human and mouse conventional CD4 T (Tconv) cells revealed that TCF1 protects Tconv cells from inadvertent Foxp3 expression. Our data implicate a role of TCF1 in suppressing Foxp3 expression in activated T cells.
Gesehen am 29.03.2021